Double-seedlings and embryo-free seeds generated by genetic engineering - Xia, Yumei; Wang, Yao; Hu, Yuanyi; Zhan, Yijie; Dan, Junhao; Tang, Ning; Tian, Junyou; Cao, Mengliang (Frontiers in Plant Science, 2022)
Apomixis can fix the heterosis of Hybrid F1, by maintaining its heterozygous genotype, and is an ideal way for the development of hybrid rice. In this paper, we designed an engineering strategy for realizing apomictic reproduction of hybrid rice in the way of induce adventitious embryos. An embryogenesis gene, AtWUS, controlled by the ovule-specific promoter, a ribonuclease gene Barnase driven by the egg cell-specific promoter pDD45, and an inactivation gene ZmAA1 driven by the pollen-specific promoter pG47 were simultaneously integrated into one T-DNA, and co-transformed with the second T-DNA carrying a Barstar gene. Double-seedlings were observed in transgenic line. Whole-genome sequencing and ploidy levels confirmed by flow cytometry showed that one of the double-seedlings was heterozygous diploid and the other seedling was homozygous haploid, which confirmed that embryogenesis in one of the double-seedlings arises from the zygote after fertilization and the other derived from an unfertilized gamete. Meanwhile we obtained embryo-free seeds at frequencies of 2.6% to 3.8% in T1 generation, and 0.75% to 3% in T2 generation. Though we did not obtained adventitious embryos in hybrid rice in this study, the phenomenon of double-seedlings and embryo-free seeds in transgenic line was informative and strongly suggested that endosperm development is an autonomously organized process in rice, independent of egg cell fertilization and embryo-endosperm communication. This provides novel insights into the induction of haploid embryos and lends theoretical support to successful clonal propagation using synthetic apomixis